SISTEM INFORMASI PENGELOLAAN NILAI MAHASISWA BERBASIS WEB PADA STMIK STIKOM INDONESIA - Komang Kurniawan Widiartha; Made Dona Wahyu Aristana (Universitas Islam Lamongan, 2018)
The scores management system conducted by the STMIK STIKOM Indonesia institution is still done manually, where the lecturer writes in the form of physical or paper assessment which is then re-input by the staff of the Academic Administration Bureau (BAAK) into the existing system. This has an impact on the ineffectiveness and inefficiency in the process of scores management and presentation in the form of report on the recapitulation of values that require long enough for the students. It takes a computerized system in the management of values that can accelerate the process of scores management, where the lecturers directly perform input and scores management into a system that is synchronized with the academic system as well as information in the form of a report of value to the party in need. The system to be designed and built is a web-based student information management system. In this study, the main objective is to facilitate lecturers and staff in the management of student scores and manufacture of computerized assessment report recapitulation.